Striking numbers: new approaches to quantitative strike research (Amsterdam, 2012)
"Strikes in modern capitalist societies have been the subject of study since the first one occurred. Because striking was considered a breach of law, the police were the first to collect data on strikes. Strikes also being a clear expression of the ‘social question’, economists, historians and national statistical bureaus soon followed suit. Labour unions and socialist parties regarded strikes as a means to achieve power for the working classes and their organisations. They therefore also published data and the stories of strikes."